Predictive value of the systemic inflammation grade for overall survival in patients with colorectal cancer after surgery: outperforming NLR and mGPS - Wang, Jianing; Liu, Yujun; Jiang, Wenliang; Zhang, Dongli; Cheng, Chao; Liu, Cuixia; Zhao, Zhibin; Wang, Honggang (Frontiers in Oncology, 2025)
BackgroundAccurate prognostic stratification remains challenging in colorectal cancer (CRC) patients after curative resection. The Systemic Inflammation Grade (SIG), integrating neutrophil-to-lymphocyte ratio (NLR) and modified Glasgow Prognostic Score (mGPS), was proposed as a composite marker to refine risk assessment.MethodsThis retrospective study analyzed 263 CRC patients undergoing R0 resection (2015–2019). Preoperative NLR and mGPS were calculated, and SIG was categorized into low (0), medium (1), and high (≥2) groups. Associations between SIG and clinicopathological variables, chemotherapy compliance, and overall survival (OS) were evaluated using ROC analysis, Kaplan-Meier curves, and Cox regression. Subgroup analyses stratified by tumor location (colon vs. rectum) were performed to assess prognostic heterogeneity.ResultsHigher SIG scores correlated with elevated CEA (P=0.002), advanced TNM stage (P=0.001), and reduced chemotherapy compliance (64.0% non-compliant patients had SIG≥2, P<0.001). Multivariate analysis identified SIG (HR=2.24, P<0.001), CEA, tumor differentiation, and TNM stage as independent prognostic factors. SIG demonstrated superior prognostic accuracy (AUC=0.785) compared to NLR (0.713), mGPS (0.673), and TNM staging (0.675). Kaplan-Meier analysis revealed significant survival differences across SIG groups (5-year OS: 90.9% vs. 76.4% vs. 37.0%, P<0.001) and additional stratification within TNM stages. Subgroup analysis showed consistent prognostic efficacy of SIG in both colon and rectal cancers, with no significant interaction between SIG and tumor location (P=0.309).ConclusionsSIG outperforms existing biomarkers and complements TNM staging by capturing systemic inflammation-driven risk heterogeneity. Its prognostic consistency across colon and rectal cancers supports its utility as a universal tool for postoperative risk stratification, guiding personalized adjuvant therapy and surveillance strategies.